Rickettsia sp. DNA recovered from a febrile patient from Papua, Indonesia - Edison Johar; Ida Yus Sriyani; Yora Permata Dewi; Agatha Mia Puspitasari; Fahira Ainun Nisa; Ristya Amalia; Pinkan Pertiwi Kariodimedjo; Jeanne Rini Poespoprodjo; Enny Kenangalem; Frilasita Aisyah Yudhaputri; Leily Trianty; Jeremy P. Ledermann; et al. (IDCases, 2025)
Background: Rickettsia are neglected, arthropod-borne bacteria causing febrile illness of varying severity. Indonesia is endemic for several Rickettsia species, predominantly from murine and scrub typhus groups. Objective: We described here a potentially novel Rickettsia species in a young adult presenting with acute, undifferentiated, febrile illness at a primary health center in Timika, Papua, Indonesia, in 2021. Methods: Blood tested positive for Rickettsia spp. by a nucleic acid amplification test, 17-kDa and ompB gene fragments were successfully sequenced. Results: The recovered sequences showed the highest similarity to two Rickettsia spp. of mosquito origin, with 90.0% identity for the 17-kDa and 85.6% for the ompB gene. Conclusion: These findings suggest the presence of a divergent Rickettsia lineage in Papua, Indonesia. To our knowledge, this is the first report of Rickettsia DNA sequences obtained from a human case in this region.